2015
DOI: 10.1128/aem.03322-14
|View full text |Cite
|
Sign up to set email alerts
|

MS2 Virus Inactivation by Atmospheric-Pressure Cold Plasma Using Different Gas Carriers and Power Levels

Abstract: In this study, airborne MS2 bacteriophages were exposed for subsecond time intervals to atmospheric-pressure cold plasma (APCP) produced using different power levels (20, 24, and 28 W) and gas carriers (ambient air, Ar-O 2 [2%, vol/vol], and He-O 2 [2%, vol/vol]). In addition, waterborne MS2 viruses were directly subjected to the APCP treatment for up to 3 min. MS2 viruses with and without the APCP exposure were examined by scanning electron microscopy (SEM), reverse transcription-PCR (RT-PCR), and sodium dode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…When the plasma generation area was reduced by 25%, the reactor's E. coli inactivation efficiency reduced significantly to 29% (0.16 log reduction) [19]. Wu et al applied a 14 kV 10 kHz AC power supply, and at 20 W power level, the reactor achieved ~80% MS2 inactivation (0.9 log reduction) in room air during a 0.12 s treatment time [18]. Both of these studies, however, only reported the reductions of viable bioaerosol concentration after the NTP treatment, and did not separate the inactivation effect of the active plasma species from the physical electrostatic precipitation or filtering effect of the reactor.…”
Section: Ms2 Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the plasma generation area was reduced by 25%, the reactor's E. coli inactivation efficiency reduced significantly to 29% (0.16 log reduction) [19]. Wu et al applied a 14 kV 10 kHz AC power supply, and at 20 W power level, the reactor achieved ~80% MS2 inactivation (0.9 log reduction) in room air during a 0.12 s treatment time [18]. Both of these studies, however, only reported the reductions of viable bioaerosol concentration after the NTP treatment, and did not separate the inactivation effect of the active plasma species from the physical electrostatic precipitation or filtering effect of the reactor.…”
Section: Ms2 Inactivationmentioning
confidence: 99%
“…Researchers [17,18] have reported reductions in infective airborne pathogen concentrations as a result of NTP treatment, results that included confounding effects of extended exposure of viral aerosols to ozone [17] or loss of viral aerosols by charge-driven filtration [18]. In one study, a DBD NTP reactor with 10 s plasma exposure and a very high air flow rate (25 l s −1 ) resulted in 97% Escherichia coli inactivation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the UAV remote-sensing (UAV-RS) approach has been frequently reported as advantageous over spaceborne and traditional airborne remote-sensing approaches due to the resultant high temporal and spatial resolution data as well as the survey cost efficiency associated with this approach (Femondimo et al 2011;Müllerová et al 2017;Babapour et al, 2017). Applications of the UAV-RS approach include inter alia agriculture , precision agriculture (Primicerio et al 2012;Gómez-Candón, De Castro, and Lopez-Granados 2014;Rokhmana 2015;Bagheri 2017), land use (Akar 2017), forestry (Thiel and Schmullius 2017;Torrescan et al 2017), archaeology (Rinaudo et al 2012;Fernández-Hernandez González-Aguiler, Rodriguez-Gonzalvez, and Mancera-Taboada 2015), classification of native vegetation (Zhang 2014), and mapping of invasive alien plants (IAPs) (Dvořák et al 2015;Müllerová et al 2016;Hill et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as another method of air-sterilization, NTP has been investigated in previous studies (3,128,130,131). It is more advantageous over other methods as it does not produce secondary environmental pollution and is cost effective (132).…”
Section: Ntp Inactivates Bio-aerosols Rapidly and Facilitates A Diseamentioning
confidence: 99%